Case-control study of paternal occupational exposures and childhood bone tumours and soft tissue sarcomas in Great Britain, 1962-2010 - Kendall, G; Bunch, K; Stiller, C; Vincent, T; Murphy, M (Springer Nature, 2020)
Background: This nationwide study investigated associations between paternal occupational exposure and childhood bone tumours and soft- tissue sarcomas. Methods: The UK National Registry of Childhood Tumours provided cases of childhood sarcomas born and diagnosed in Great Britain, 1962–2010. Control births, unaffected by childhood cancer, were matched on sex, birth period and birth registration sub-district. Fathers’ occupations were assigned to one or more of 33 exposure groups and coded for occupational social class. Results: We analysed 5,369 childhood sarcoma cases and 5380 controls. Total bone tumours, total soft-tissue sarcomas and the subgroups osteosarcoma, rhabdomyosarcoma and Ewing Sarcoma Family of Tumours (ESFT) were considered separately. Significant positive associations were seen between rhabdomyosarcoma and paternal exposure to EMFs (odds ratio = 1.67, CI = 1.22–2.28) and also for ESFT and textile dust (1.93, 1.01–3.63). There were putative protective effects on total bone tumours of paternal dermal exposure to hydrocarbons, metal, metal working or oil mists. Conclusions: Despite the large size and freedom from bias of this study, our results should be interpreted with caution. Many significance tests were undertaken, and chance findings are to be expected. Nevertheless, our finding of associations between ESFT and paternal exposure to textile dust may support related suggestions in the literature.